Development of Logical Reasoning in High School Students in Lima, Peru: Evaluating the Impact of Logic Workshops in Schools Without Prior Instruction - Mora Ramirez, Rafael Félix (2024)
The objective of this study is to determine whether students from schools where logic is not taught can pass the subject after participating in a workshop designed to reinforce their logical reasoning. Methodologically, the study employed a quantitative approach and was conducted as a quasi-experimental investigation at an explanatory level. This study was based on non-probabilistic sampling, specifically, convenience sampling. After applying exclusion criteria, the sample comprised 43 students who attended all sessions of the logic workshop conducted in the selected schools. The study investigated the retention of logical knowledge by these students through a three-week workshop, followed by a comprehensive assessment covering both formal and informal logic. Despite the lack of normality, Friedman's test revealed significant differences between the three data sets, indicating progress in grades throughout the study. It is concluded that if the grades of the three exit tests are compared, some progress is observed, indicating student understanding of the course. However, the low average grade obtained by the students in the final exam indicates that overall, there was a deficient understanding of the logic, perhaps because there was little time for review and, in addition, there were too many concepts involved. Nonetheless, the fact that some students achieved scores as high as 18 out of 20 indicates that the final test was manageable. Overall, the average grade suggests that the logic course is passable, and students were able to recognize and assimilate logical content, facilitating the development of their creative and original thinking skills. Based on these findings, it is recommended to consider the reintroduction of logic as a compulsory subject in basic secondary education throughout Peru.